EFFECTS OF PATIENT QUESTION PROMPT LIST USE ON PARTICIPATION DURING OUTPATIENT PALLIATIVE CARE APPOINTMENTS. (20th December 2022) - McDarby, Meghan; Silverstein, Hannah; Carpenter, Brian
Abstract: Question prompt lists (QPLs) support patients who are seeking information during medical appointments by providing preset questions a patient might ask their provider. Prior research suggests that QPLs promote communication, including question asking, during appointments. The current study evaluated use of a 25-question QPL during initial outpatient palliative care appointments. We applied tenets of Social Cognitive Theory to investigate the relation between question asking and self-efficacy. Participants were patients attending their first outpatient palliative care appointment at an academic hospital. Participants were randomly assigned to receive the QPL before their appointment (n = 29) or to receive usual care (n = 30). Audio recordings of appointments were transcribed and coded for total questions asked. Participants also responded to a single-item measure of self-efficacy in question asking at pre- and post-appointment. On average, participants in usual care appointments asked 9.37 questions (SD = 10.3, range= 0 – 49), and participants in QPL appointments asked 11.24 questions (SD = 10.1, range = 0 – 45), but with no significant difference between groups, F(1, 56) = 0.14, p = .71. All participants reported an increase in self-efficacy from pre- to post-assessment, F(1, 83) = 18.76, p < .00, but there was no interaction effect of time and condition, F(1, 83) = .81, p = .37. Despite their promise in previous studies, our results suggest QPLs may lack potency to shift question asking, at least in palliative care appointments, and that other mechanisms of Social Cognitive Theory may better characterize the relation between question asking and self-efficacy.